2016
DOI: 10.1021/acs.est.6b04059
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Capabilities of in Vitro Assays for Estimating Pb Relative Bioavailability in Phosphate Amended Soils

Abstract: In this study, the in vitro bioaccessibility (IVBA) of lead (Pb) in phosphate-amended Pb-contaminated soil was assessed using a variety of IVBA assays with an overarching aim of determining whether changes in Pb IVBA were congruent to those observed for Pb relative bioavailability (RBA) determined using an in vivo mouse assay. Amending soil with phosphoric acid or rock phosphate resulted in changes in Pb speciation, however, varying Pb IVBA results were obtained depending on the methodology utilized. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 47 publications
1
24
0
Order By: Relevance
“…Pb IVBA in unamended soil was 88.6±0.8% when assessed in the SBRC-G phase ( Figure 1A). No significant reduction (P>0.05; Figure 1A) in Pb IVBA was observed in P and Fe amended soil (TER=1.02-1.08; Table S3) using SBRC-G phase, which is similar to the results reported for amended mining soil when assessed at pH 1.5 16,53,54 . Pb speciation in SBRC-G residual soil identified that the majority of anglesite was solubilized ( Figure 1B), which was expected due to anglesite's propensity for solubilization under low pH conditions 48 .…”
Section: Treatment Efficacy -Ingestion Pathway Pb Ivba and Residual Psupporting
confidence: 82%
“…Pb IVBA in unamended soil was 88.6±0.8% when assessed in the SBRC-G phase ( Figure 1A). No significant reduction (P>0.05; Figure 1A) in Pb IVBA was observed in P and Fe amended soil (TER=1.02-1.08; Table S3) using SBRC-G phase, which is similar to the results reported for amended mining soil when assessed at pH 1.5 16,53,54 . Pb speciation in SBRC-G residual soil identified that the majority of anglesite was solubilized ( Figure 1B), which was expected due to anglesite's propensity for solubilization under low pH conditions 48 .…”
Section: Treatment Efficacy -Ingestion Pathway Pb Ivba and Residual Psupporting
confidence: 82%
“…For example, among 179 As-contaminated soils, 47 soils have data for As-IVIVCs by all 5 assays Juhasz et al, 2011;Juhasz et al, 2015;Bradham et al, 2011;Li, Li, Cui, et al, 2015). For 140 Pb-contaminated soils, only 20 soils have data for Pb-IVIVCs by all 5 assays (Juhasz et al, 2016;Li, Li, Cave, et al, 2015;Li, Liu, et al, 2017). Similarly, out of 45 Cd-contaminated soils, only 19 soils have data for Cd-IVIVCs by 4 assays (Juhasz et al, 2010;.…”
Section: Limitations To Existing Ivivcsmentioning
confidence: 99%
“…To ensure the robustness of in vitro assays, IVIVC validation using independent soils is needed. In addition, IVIVC studies have focused on contaminated soils, with limited studies assessing their reliability to predict metal bioavailability in remediated soils (Juhasz et al, 2016). This will attract increasing interests as more contaminated sites are being remediated (Bradham, Diamond, Nelson, et al, 2018).…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Studies have reported TER range from P-treated soils as a minimum of 0.08 [5] to maximum of 1.16 [30] with a median value of 0.78. A TER value of one indicates that the treatment had no effect on Pb bioaccessibility; a TER value of <1 indicates a decrease in Pb bioaccessibility due to treatment effect [31]. Median TER results indicated that P-amendments reduced Pb bioaccessibility but not significantly [5,30].…”
Section: Assessment Of Pb and As Bioaccessibilitymentioning
confidence: 99%